Do Analysts and Investors Efficiently Respond to Managerial Linguistic Complexity during Conference Calls? - Bushee, Brian J.; Huang, Ying (The Accounting Review, 2024)
ABSTRACT This paper examines whether analysts and investors efficiently incorporate the informational signals from managerial linguistic complexity (e.g., Fog) into their forecasts and trading decisions. We predict that a manager’s Fog during a conference call provides a signal of their private information through their willingness to engage with analyst questions. We find that informative (obfuscatory) managerial Fog provides a positive (negative) signal of future earnings growth. We also find that analysts efficiently revise their forecasts to both positive and negative signals, whereas investors only correctly interpret obfuscation during the call; there is a delayed price reaction to informative Fog. However, when buy-side investors ask questions during a call, we find an efficient price reaction to informative Fog. Our findings highlight an important benefit of two-way interactive disclosures and underline the importance of active call participation for efficiently incorporating linguistic signals of managers’ private information. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: D82; G14; G20; M41.